У пошуках iдентичностi: Героïня украïнськоï жiночоï прози рубежа ХХ-ХХ1 ст. - Betko, Iryna (Acta Polono-Ruthenica, 2008)
One of the most unusual events in the Ukrinian new wave literature is massive return women in it, which began in the end of 80-es. Among the most interesting writers there must be mentioned Oksana Zabuzhko, Svitlana Kasjanova, Jevhenia Kononenko, Sofia Majdanska, Valentyna Masterova, Halyna Pahutiak, Lubov Ponomarenko, Natalka Śniadanko and others. In the works of these authors, written from the femine and feministic position, as opposite to patriarchal-maskuline mentality, are deeply and convincingly considered the aspects of modern human exsistence: loneliness and alienation, loss of identity, lack of mutual understanding even among fellows and relatives, egoism and egocentism, various forms of physical and phsychological agression, and so on. Espacially great attention author of this article devotes to the analysis of chosen aspects of female identyty in the works of Zabuzhko (Field Exploration in Ukrainian Sex and others), Śniadanko (Collection of Pasions or Adventures ofYoung Ukrainian Lady), Kononenko (Without Fellow).